Calanoid Copepods: An Overlooked Tool in the Control of Disease Vector Mosquitoes. Issue 6 (1st August 2018) - Cuthbert, Ross N; Dalu, Tatenda; Wasserman, Ryan J; Callaghan, Amanda; Weyl, Olaf L F; Dick, Jaimie T A
Abstract: Biological control can assist in the management of disease vector mosquitoes. However, we urgently require the identification of novel and effective agents to aid population management strategies. Previously, predatory biocontrol of disease vector mosquito species has focused extensively on cyclopoid copepods, but prey size refuge effects have been identified as a hindrance to their predatory efficacy. Calanoid copepods have yet to be examined in the context of mosquito control, despite their high prevalence, diversity, and distribution. Here, we apply functional responses (FRs; resource use as a function of resource density) to examine predation efficiencies of a recently described ephemeral pond specialist species, the freshwater calanoid copepod Lovenula raynerae Suárez-Morales, Wasserman & Dalu 2015 (Calanoida: Diaptomidae), using different size classes of larvae of the disease vector complex Culex pipiens (Diptera: Culicidae) as prey. Lovenula raynerae effectively consumed Cx. pipiens larvae across their ontogeny. A potentially population destabilizing type II FR was exhibited toward both early and late instar mosquitoes, indicative of a lack of prey refuge across ontogenetic stages. Attack rates were greatest and handling times lowest for early instar larvae compared to late instar larvae. These traits contrast to other copepods commonly applied in biocontrol, which are only able to handle early instars, and in much smaller numbers. We thus advocate that calanoid copepods can exert particularly marked predatory impact on lower trophic groups, and that their use in disease vector mosquito control strategies should be further explored.